1,4-Bis(1H-benzimidazol-1-yl)benzene - Guo-Feng Sun (Acta Crystallographica Section E, 2011)
In the title compound, C20H14N4, the dihedral angles between the central benzene ring and the pendant benzimidazole ring systems are 46.60 (15) and 47.89 (16)°. The dihedral angle between the benzimidazole ring systems is 85.62 (12)° and the N atoms lie to the same side of the molecule. In the crystal, molecules are linked by C—H...N interactions and weak aromatic π–π stacking [shortest centroid–centroid separation = 3.770 (2) Å] is observed.